Outcomes of systemic targeted therapy in recurrent renal cell carcinoma treated with adjuvant sunitinib. (19th April 2021) - de Velasco, Guillermo; Ruiz‐Granados, Álvaro; Reig, Oscar; Massari, Francesco; Climent Duran, Miguel Angel; Verzoni, Elena; Graham, Jeffrey; Llarena, Roberto; De Tursi, Michele; Donskov, Frede; Iglesias, Clara; Pandha, Hardev S.; et al.
Abstract : Objective: To assess the efficacy and tolerability of rechallenge with sunitinib and other targeted therapies (TTs) in patitents with relapsed recurrent renal cell carcinoma (RCC) in the advanced setting. Methods: In this multi‐institutional retrospective study, patients with relapsed RCC were rechallenged with sunitinib or other systemic TTs as a first‐line therapeutic approach after failed adjuvant sunitinib treatment. Patient characteristics, treatments and clinical outcomes were recorded. The primary endpoint was progression‐free survival (PFS). Secondary endpoints were objective response rate (ORR) and overall survival (OS). Results: A total of 34 patients with relapses were recorded, and 25 of these (73.5%) were men. Twenty‐five patients were treated with systemic TT: 65% of patients received TT against the vascular endothelial growth factor pathway (including sunitinib), 21.7% received mammalian target of rapamycin inhibitors and 13% received immunotherapy. The median (interquartile range) time to relapse was 20.3 (5.2–20.4) months from diagnosis, and 7.5 months (1.0–8.5) from the end of adjuvant suntinib treatment. At a median follow‐up of 23.5 months, 24 of the 25 patients had progressed on first‐line systemic therapy. The median PFS was 12.0 months (95% confidence interval [CI] 5.78–18.2). There were no statistical differences in PFS between different treatments or sunitinib rechallenge. PFS was not statistically different in patients relapsing on or after adjuvant suntinib treatment (≤ 6 or >6 months after adjuvant suntinib ending). The ORR was 20.5%. The median OS was 29.1 months (95% CI 16.4–41.8). Conclusions: Rechallenge with sunitinib or other systemic therapies is still a feasible therapeutic option that provides patients with advanced or metastastic RCC with additional clinical benefits with regard to PFS and OS after failed response to adjuvant sunitinib.